Feasibility and Patients’ Acceptance of Home Automated Telemanagement of Oral Anticoagulation Therapy - Finkelstein, J (American Medical Informatics Association, 2003)
We developed the Home Automated Telemanagement (HAT) system for patients on oral anticoagulation therapy. It consists of a home unit, HAT server, and clinician unit. Patients at home use a palmtop or a laptop connected with a prothrombin time (PT) monitor. Each HAT session consists of self-testing, feedback, and educational components. The symptom data and PT/INR from patient homes are automatically sent to the HAT server and analyzed by the system. Patients who were seen in the Anticoagulation Clinic (N=29) were asked to use HAT in a laboratory setting. Semi-structured, indepth interviews were used for the evaluation of HAT acceptance. 93% claimed that they would use such a tool at home and would advise other patients to use HAT for self-management and disease-specific education. Twelve patients used HAT at home for eight weeks. Compared to baseline, patients completing the home study showed statistically significant improvement in disease-specific quality of life dimensions of general satisfaction, self-efficacy, daily hassles, and distress. The Client Satisfaction Questionnaire demonstrated significant improvement in patient satisfaction with the treatment process. Our results demonstrated high acceptance of the HAT system by patients receiving long term anticoagulation therapy regardless of their previous computer experience or socioeconomic background.